Parallel Helix Actuators for Soft Robotic Applications - Chandler, James H.; Chauhan, Manish; Garbin, Nicolo; Obstein, Keith L.; Valdastri, Pietro (Frontiers in Robotics and AI, 2020)
Fabrication of soft pneumatic bending actuators typically involves multiple steps to accommodate for the formation of complex internal geometry and the alignment and bonding between soft and inextensible materials. The complexity of these processes intensifies when applied to multi-chamber and small-scale (~10 mm diameter) designs, resulting in poor repeatability. Designs regularly rely on combing multiple prefabricated single chamber actuators, or are limited to simple (fixed cross-section) internal chamber geometry which can result in excessive ballooning and reduced bending efficiency; compelling the addition of constraining materials. In this work, we address existing limitations by presenting a single material molding technique that uses parallel cores with helical features. We demonstrate that through specific orientation and alignment of these internal structures, small diameter actuators may be fabricated with complex internal geometry in a single material–¬without¬ additional design critical steps. The helix design produces wall profiles that restrict radial expansion while allowing compact designs through chamber interlocking, and simplified demolding. We present and evaluate three-chambered designs with varied helical features; demonstrating appreciable bending angles (>180 degrees), three-dimensional workspace coverage and 3x bodyweight carrying capability. Through application and validation of the constant curvature assumption, forward kinematic models are presented for the actuator and calibrated to account for chamber-specific bending characteristics; resulting in a mean model tip error of 4.1 mm. This simple and inexpensive fabrication technique has potential to be scaled in size and chamber numbers, allowing for application specific designs for soft, high-mobility actuators especially for surgical or locomotion applications.